CHALLENGES OF EFFECTIVE LABOR RESOURCE UTILIZATION IN ENHANCING POPULATION EMPLOYMENT - Tokhtasinova Dildora Rakhmonberdiyevna (International Journal of Literature and Language Studies, 2026)
This study explores the efficient utilization of labor resources as a key determinant of employment growth in Uzbekistan. The research employs descriptive statistical methods, comparative regional analysis, and policy evaluation techniques to examine changes in employment indicators across Uzbekistan and its regions during 2020–2024. The findings reveal that the national employment rate rose from 66.0% in 2020 to 68.3% in 2024; however, significant disparities persist among regions. The most substantial improvements were recorded in the Kashkadarya and Tashkent regions, while slight decreases were identified in Bukhara, Jizzakh, and Surkhandarya. The results suggest that employment strategies should extend beyond overall job creation and incorporate measures such as the development of regional specialization, the formalization of informal economic activities, professional retraining initiatives, support for women’s and youth employment, enhancement of digital competencies, and stimulation of private-sector employment opportunities. The article offers practical policy recommendations aimed at strengthening labor resource management under conditions of demographic growth and ongoing digital transformation.